Identification and Characterization of Genetic Variants in the Human ACAN Gene Using the ClinVar Database - Arielda Putri Aditya; Wolly Candramila (Tropical Genetics, 2026)
The ACAN gene plays an important role in skeletal growth and development, so mutations in this gene are associated with various disorders such as short stature and skeletal dysplasia. This study aims to identify and characterize ACAN gene mutation variations using the ClinVar database at the National Center for Biotechnology Information to support the interpretation of pathogenicity and genetic diagnosis. This study was conducted in silico with a descriptive-comparative approach using ACAN gene variant data from the ClinVar database at the National Center for Biotechnology Information. Pathogenic and likely pathogenic variants were analyzed and grouped based on germline classification, molecular consequence, and variation type. The results of the ClinVar database analysis at the National Center for Biotechnology Information showed that most ACAN gene variants are categorized as pathogenic, with missense variants, frameshift variants, and single-nucleotide variants as the most dominant mutation types found. Genetic variations in the ACAN gene have a strong clinical association with skeletal growth disorders, especially short stature, so that ACAN gene variant analysis has the potential to support genetic diagnosis, prognosis, and genetic counselling in skeletal disorders. This study also shows that the use of bioinformatics databases can help understand the relationship between genetic variation and disease more systematically.